ISLAMIC ECONOMIC VIEWS ON THE CONCEPT OF JUSTICE IN THE DISTRIBUTION OF INHERITANCE FOR DAUGHTERS IN THE PAKPAK TRIBAL COMMUNITY - Nazli Hasan; Falahuddin; Fuadi; Isniati Berasa; Rico Nur Ilham (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This research examines the forms of habits in the Pakpak people, precisely in Maholida Village, in the form of an injustice system in inheritance experienced by girls, as well as examines the Islamic economic view of injustice that benefits men and the weakness of the inheritance system for girls in the distribution of wealth in society pack tribe. The population in this study were all Pakpak people in Maholida Village with a total sample of (11) people consisting of representatives of religious leaders, government leaders, traditional leaders and representatives of the Pakpak people. With his research using qualitative analysis methods by conducting direct interviews with respondents to get answers to the problems studied. The results of the study indicate that there is a concept of injustice in the distribution of inheritance to daughters in the Pakpak tribe which benefits one party and harms the other party in a family.